2016
DOI: 10.1074/jbc.m115.705541
|View full text |Cite
|
Sign up to set email alerts
|

Monoacylglycerol Lipases Act as Evolutionarily Conserved Regulators of Non-oxidative Ethanol Metabolism

Abstract: Fatty acid ethyl esters (FAEEs) are non-oxidative metabolites of ethanol that accumulate in human tissues upon ethanol intake. Although FAEEs are considered as toxic metabolites causing cellular dysfunction and tissue damage, the enzymology of FAEE metabolism remains poorly understood. In this study, we used a biochemical screen in Saccharomyces cerevisiae to identify and characterize putative hydrolases involved in FAEE catabolism. We found that Yju3p, the functional orthologue of mammalian monoacylglycerol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 66 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…Recent data suggest that MGL also degrades prostaglandin glycerol esters, which represent still poorly characterized inflammatory mediators (Savinainen et al, 2014). Finally, MGL has been implicated in non-oxidative ethanol metabolism by hydrolyzing fatty acid ethyl esters which are produced in the body in response to alcohol consumption (Heier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that MGL also degrades prostaglandin glycerol esters, which represent still poorly characterized inflammatory mediators (Savinainen et al, 2014). Finally, MGL has been implicated in non-oxidative ethanol metabolism by hydrolyzing fatty acid ethyl esters which are produced in the body in response to alcohol consumption (Heier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, MGL as well as FAEE were found to associate with lipid droplets (LDs), which are cellular storage organelles of hydrophobic esters such as triacylglycerol or steryl esters. This suggests that FAEE are transiently stored in LDs and hydrolyzed by LD‐associated MGL .…”
Section: Fatty Acid Ethyl Estermentioning
confidence: 99%
“…FAEEH activities have been measured in a multitude of tissues, and highest activities have been observed in pancreas and liver . Several serine hydrolases with FAEEH activity have been identified including hepatic carboxylesterase isoforms, hormone‐sensitive lipase and monoacylglycerol lipase (MGL) . Based on the abundance of carboxylesterase isoforms Diczfalusy et al concluded that Es‐4 (also known as Ces1f) may be responsible for a considerable portion of rat hepatic FAEEH activity.…”
Section: Fatty Acid Ethyl Estermentioning
confidence: 99%
“…MGL is ubiquitously expressed among tissues, with slightly different molecular sizes [175]. The enzyme exhibits high hydrolytic activity against MAGs [176]; however, it was also shown to hydrolyze prostaglandin glycerol esters [177] and FA ethyl esters [178].…”
Section: Mgl and Its Interaction Partnersmentioning
confidence: 99%